Fatiga, expectativas y calidad de vida en cáncer - Buscemi, Valerie; Font, Antoni; Rodríguez, Eva (Psicooncología, 2004)
Fatigue is a highly prevalent condition that reduces quality of life among cancer patients. About 80 % show some degree of fatigue along the clinical phases of the disease. Fatigue is a complex-subjective syndrome with bio-psycho-social aspects, and could be present many years after the end of the treatment. Objective factors like the kind of biological treatment or the stage of the disease can’t explain the wide patients´ variability about this syndrome. In addition, many psychosocial variables as catastrophizing, stress or social support have been proposed. This paper contributes with some data about fatigue in different diseases stages and the role of the expectations. In a sample of 215 breast cancer patients we find a relationship between fatigue and illness stadium: patients in diagnose phase showed less fatigue (mean = 18,5) than them with adjuvant therapy (mean = 22,4) or the patients in the recidive phase (mean = 26,4). As expected, the disease-free interval patients´ group showed the lowest Fatig es´value (mean = 7,5); the higher one was found in the advanced-disease group (mean = 36,9). We found also significant relationships (P